Skeletal Manifestations of Scurvy: A Case Report from Dubai - Shahryar Noordin; Naveed Baloch; Muhammad Sohail Salat; Abdul Rashid Memon; Tashfeen Ahmad (Case Reports in Orthopedics)
Introduction. Nutritional deficiencies are rarely reported in developed countries. We report a child of Pakistani origin brought up in Dubai who developed skeletal manifestations of scurvy due to peculiar dietary habits. Case Presentation. A 4.5 year old boy presented with pain and swelling of multiple joints for three months and inability to walk for two months. Dietary history was significant for exclusive meat intake for the preceding two years. On examination the child’s height and weight were below the 5th percentile for his age. He was pale and tachycardic. There was significant swelling and tenderness over the wrist, knee and ankle joints, along with painful restriction of motion. Basic blood workup was unremarkable except for anemia. However, X-rays showed delayed bone age, severe osteopenia of the long bones, epiphyseal separation, cortical thinning and dense zone of provisional calcification, suggesting a radiological diagnosis of scurvy. The child was started on vitamin C replacement therapy. Over the following two months, the pain and swelling substantially reduced and the child became able to walk. Repeat X-rays showed improvement in the bony abnormalities. Conclusion. Although scurvy is not a very commonly encountered entity in the modern era, inappropriate dietary intake can lead to skeletal abnormalities which may be confused with rickets. A high index of suspicion is thus required for prompt diagnosis of scurvy in patients with bone and joint symptoms.